History and development of anaesthesiology (with resuscitation and intensive medicine) in the Republic of Macedonia - Vladimir Andonov; Sholjakova, Marija; Jordan Nojkov; Zorka Nikolova-Todorova; Shosholcheva, Mirjana; Kartalov, Andrijan; Kuzmanovska, Biljana (Macedonian Academy of Sciences and Arts, 2014)
Aim: To present a chronological overview of the most important events and actors that have marked the history of anaesthesiology and intensive treatment in R. Macedonia since its beginnings in the 1950s. Method: Retrospective study based on archive materials, published literature and jubilee publications, as well as the memories of individuals who have worked in the field of anaesthesiology in the past period. Results: Between the two World Wars the first anaesthesia procedures were handled by surgeons. After World War II, the development of anaesthesia in R. Macedonia could be divided into two periods: before 1965 and after 1965. Before 1965 anaesthesia was mainly given by technicians trained on courses, and after this year anaesthesiology was taken over by anaesthesiologists who had specialized at the Faculty of Medicine in Skopje. In 1985 the number of anaesthesiologists was 100, and today it exceeds 250. The most important figures in the history of Macedonian anaesthesiology are: Dr. Risto Ivanovski, who worked from 1954-78, and Prof. Dr. Vladimir Andonov, who worked as an anaesthesiologist from 1965-99. Both of them are doyens who contributed a lot to the development of the anaesthesiology service and education of anaesthesiologists in R. Macedonia. Intensive treatment had started in 1955, but in real terms it has been performed since 1966, when artificial ventilators were introduced. The modern Intensive Care Department was opened at the Surgical Clinic in 1995 and it was followed in other hospitals in the state. The Department of Anaesthesiology has existed since 1975, and it has made a huge contribution to the education of professionals who apply modern principles in emergency medicine and intensive care. Conclusion: From modest beginnings in the 1950s, anaesthesiology today in R. Macedonia has developed well organized activity that successfully follow the trends of modern medicine in the field of anesthesiology, resuscitation, intensive care and pain treatment.